1975-1976 ネン ノ ヤマト サンミャク ニ オケル ヒョウガ ソクテイ ヨウ ノ グリッド セッチ ニ ツイテ - 松本, 徰夫; マツモト, ユキオ; 真部, 充宏; マナベ, マサヒロ; 船木, 實; フナキ, ミノル; Matsumoto, Yukio; Manabe, Masahiro; Funaki, Minoru (国立極地研究所, 1977)
P(論文) 第16次南極観測隊のメンバー7名は,1975年11月12日～1976年1月24日の期間,やまと山脈までの旅行を計画し成功させた.やまと山脈には38日間滞在し,地質調査・地形調査・地形測量・やまと隕石の探索・生理学的研究の他,やまと山脈の航空写真撮影・地磁気の測定・ベルジカ山脈の航空写真撮影のため飛来したセスナの支援を行った.また,やまと隕石の集積機構を解明するために,6角形のグリッドをやまと山脈A群東方の基岩(A001,基準点No. 214)近くの裸氷上に作った.このグリッドは一辺約800 mで,中心には測点A003があり,グリッドの水平方向と垂直方向の変化が分るように設置されている. From November 12, 1975 to January 24, 1976 an oversnow traverse to the Yamato Mountains was conducted by a seven-man party of the 16th Japanese Antarctic Research Expedition for geological and geomorphological surveys, topographic surveying, search for the Yamato meteorites, and physiological investigation. Furthermore a strain grid was set up around A003 control point near Motoi Nunatak (A001 control point=No. 214) for mechanism of meteorites concentration in the Meteorite Ice Field. A brief description of the traverse and the grid, hexagonal form each side being about 800 m, is given here. departmental bulletin paper